Priorities in process algebras. - HENNESSY, MATTHEW (IEEE Computer Society, 1988)
An operational semantics for an algebraic theory of concurrency is developed that incorporates a notion of priority into the definition of the execution of actions. An equivalence based on strong observational equivalences is defined and shown to be a congruence, and a complete axiomization is given for finite terms. Several examples highlight the novelty and usefulness of the approaches
PUBLISHED
Keywords: Administrative Staff Authors